Решенија за ограничување од облогата и хидродинамичка стабилност на јаловишна брана - Mircevska Violeta (Сплит- ХрватскФакултет за Градежништво Архитектура и Геодезија; Матице Хрватске 15, HR-21000 Сплит, 2023)
The study investigates the impact of reservoir lining on the hydrodynamic stability of a tailings dam. A 3D coupled fluid-solid finite element model was used for detailed seepage analyses based on conventional flow-net and steady seepage conditions. Pore pressure, stationary seepage velocities, static liquefaction and the ratio between manifested and critical hydraulic gradients were predicted under three different lining conditions. The highest potential for internal erosion and heave was observed in the lined reservoir and starter dam scenario. Although there are environmental benefits, the incorporation of liners in dam design requires a comprehensive engineering assessment of the negative hydrodynamic effects.
Containment Lining Solutions and Hydrodynamic Stability of Tailings Dam
Keywords: hydrodynamic stability; tailings dam; stationary seepage; critical erosion zones; heave potential